2019
DOI: 10.1111/1753-0407.12956
|View full text |Cite
|
Sign up to set email alerts
|

Saxagliptin alters bile acid profiles and yields metabolic benefits in drug‐naïve overweight or obese type 2 diabetes patient

Abstract: Background The aim of the present study was to investigate the metabolic benefits of saxagliptin and its effects on serum bile acids (BAs) in normal weight and overweight/obese drug‐naïve type 2 diabetes (T2D) patients. Methods In all, 282 drug‐naïve T2D patients (123 normal weight [NW], with body mass index [BMI] between 19.0 and <25.0 kg/m2; 159 overweight/obese [OW/OB], with BMI ≥25.0 kg/m2) were enrolled in the study and treated with saxagliptin 5 mg daily for 24 weeks. Serum BAs were assayed by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…Our data demonstrated that specific gut microbiota related metabolites contributed to the interpretation of the connection between the fruit-related microbiota and T2D. Previous studies demonstrated that treatment with specific microbiota derived secondary bile acids (obeticholic acid, DCA, and GDCA) in patients with T2D improved insulin sensitivity and HbAlc, which was consistent with our present study [40,41]. Another study found that fecal sebacic acid was decreased in IBD patients [42].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated that specific gut microbiota related metabolites contributed to the interpretation of the connection between the fruit-related microbiota and T2D. Previous studies demonstrated that treatment with specific microbiota derived secondary bile acids (obeticholic acid, DCA, and GDCA) in patients with T2D improved insulin sensitivity and HbAlc, which was consistent with our present study [40,41]. Another study found that fecal sebacic acid was decreased in IBD patients [42].…”
Section: Discussionsupporting
confidence: 92%
“…25 In addition, increased serum GUDCA levels are associated with decreased hemoglobin A1c and waist circumference in patients with T2DM. 26 The above evidence…”
Section: Discussionmentioning
confidence: 87%
“… 25 In addition, increased serum GUDCA levels are associated with decreased hemoglobin A1c and waist circumference in patients with T2DM. 26 The above evidence indicates that GUDCA has potential metabolic beneficial effects. However, in our study, GUDCA level in the GDM group was increased and positively correlated with blood glucose and triglyceride levels.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to the work of Humbert et al., phospholipid‐depletion SPE was shown by other groups to give higher recovery and reproducibility than protein precipitation and reversed‐phase SPE [20,31]. Alternative sample preparation methods include those omitting the SPE step, for instance, incubation of samples at low temperatures with ice‐cold methanol and centrifugation [32], lyophilization [10,33,34], or ultrafiltration [35]. Sun et al.…”
Section: Bile Acid Analysismentioning
confidence: 99%